2019
DOI: 10.1016/j.eurpsy.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The predictive capacity of DSM-5 symptom severity and impulsivity on response to cognitive-behavioral therapy for gambling disorder: A 2-year longitudinal study

Abstract: Background:DSM-5 proposed a new operational system by using the number of fulfilled criteria as an indicator of gambling disorder severity. This method has proven to be controversial among researchers and clinicians alike, due to the lack of studies indicating whether severity, as measured by these criteria, is clinically relevant in terms of treatment outcome. Additionally, numerous studies have highlighted the associations between gambling disorder and impulsivity, though few have examined the impact of impu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 63 publications
5
24
1
Order By: Relevance
“…Finally, a significant association was found between GD severity and two of the impulsivity facets, impulsive tendencies and choice impulsivity, which is consistent with other findings 24,40 . Even though a recent meta-analysis identified associations between motor impulsivity and GD 9 , our study failed to identify a significant association between response inhibition and GD severity among GD patients.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Finally, a significant association was found between GD severity and two of the impulsivity facets, impulsive tendencies and choice impulsivity, which is consistent with other findings 24,40 . Even though a recent meta-analysis identified associations between motor impulsivity and GD 9 , our study failed to identify a significant association between response inhibition and GD severity among GD patients.…”
Section: Discussionsupporting
confidence: 90%
“…It also remains unclear whether impulsivity levels are associated with treatment outcome. Some research has found high levels of impulsive traits to be associated with relapse and dropout from treatment 40 , whereas other studies have found greater awareness of gambling-related problems to be associated with positive outcomes 44 . Finally, another study found GD to be associated with response impulsivity and choice impulsivity, although only the latter was linked with GD severity 13 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 Overall, research demonstrates that CBT can have robust short-term and long-term effects on problem gambling, and related harms (e.g., quality of life, emotional wellbeing) 5,6 across gambling types 5 and severity levels. 7 Research comparing outcomes from routine clinical CBT with the results of randomised control trials (RCTs) demonstrate that CBT is as effective at addressing gambling problems and related harms in real clinical contexts, as it is in research contexts. 8…”
Section: Overall Efficacy Of Cbt For Treating Gambling Problemsmentioning
confidence: 99%
“…› A study of adult men seeking treatment for gambling disorder did not find differences in CBT outcomes between patients categorised by the American Psychiatric Association's Diagnostic and Statistical Manual of Mental Disorders, 5th edition (DSM-5) severity levels. 7 Primary Gambling Activity › A 2009 systematic review and meta-analysis found that CBT was effective at reducing problem gambling (assessed using various screening tools, SOGS most frequently used) across primary gambling activities (at three and six-month windows, excluding scratch cards at the three-month window). 5 › A 2018 study of treatment-seeking adults in London (UK) found significant differences in dropout rates depending on gambling activity.…”
Section: Severity Levelmentioning
confidence: 99%